2022
DOI: 10.3389/fneur.2022.878313
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Remote Monitoring in Evaluating Fatigue in Multiple Sclerosis: A Review

Abstract: Fatigue is one of the most common multiple sclerosis (MS) symptoms. Despite this, monitoring and measuring fatigue (subjective lack of energy)– and fatigability (objectively measurable and quantifiable performance decline)– in people with MS have remained challenging. Traditionally, administration of self-report questionnaires during in-person visits has been used to measure fatigue. However, remote measurement and monitoring of fatigue and fatigability have become feasible in the past decade. Traditional ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Throughout the study, HCPs expressed optimism about the opportunities provided by a mHealth solution like the More Stamina app to gain a better understanding of their patients, particularly regarding factors influencing fatigue, a prevalent and debilitating symptom of MS. 27 This finding aligns with recent research in MS, which has shown that employing mHealth solutions can enable HCPs to understand patients' fatigue levels and their response to treatment. 43 The validation of the habits and lifestyle being the most useful types of PGHD for HCPs relates to the principle of precision medicine, where care is personalized based on individual variability, including factors such as the patient's environment and lifestyle. 44 These factors can provide context to clinical data and facilitate communication and care.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the study, HCPs expressed optimism about the opportunities provided by a mHealth solution like the More Stamina app to gain a better understanding of their patients, particularly regarding factors influencing fatigue, a prevalent and debilitating symptom of MS. 27 This finding aligns with recent research in MS, which has shown that employing mHealth solutions can enable HCPs to understand patients' fatigue levels and their response to treatment. 43 The validation of the habits and lifestyle being the most useful types of PGHD for HCPs relates to the principle of precision medicine, where care is personalized based on individual variability, including factors such as the patient's environment and lifestyle. 44 These factors can provide context to clinical data and facilitate communication and care.…”
Section: Discussionmentioning
confidence: 99%
“…Not only apps measuring fatigue through questionnaires but also wearable devices have proved to be useful in the continuous monitoring of fatigued MS patients (Sparaco et al, 2018 ; Tong et al, 2019 ; Block et al, 2022 ). These “health technologies” usually have an internet or smartphone connection and therefore allow non-stop collection of data about physiological parameters (e.g., heart rate, sleep levels) and track any kind of physical activities through accelerometers and sensors (Sparaco et al, 2018 ).…”
Section: The Concept Of Digital Assessment and Management Of Multiple...mentioning
confidence: 99%
“…Infrequent and intermittent monitoring as provided at office visits may not truly reflect the day-to-day functioning and quality of life of patients living with MS [2]. Persons with MS may also have recall bias when reporting symptoms to their neurologist [2].…”
Section: Introductionmentioning
confidence: 99%
“…Infrequent and intermittent monitoring as provided at office visits may not truly reflect the day-to-day functioning and quality of life of patients living with MS [2]. Persons with MS may also have recall bias when reporting symptoms to their neurologist [2]. Additionally, symptoms in MS can fluctuate depending on fatigue, mood, and weather; thus, the cross-sectional nature of the information obtained from an individual clinic visit may be of limited accuracy compared with trends in symptoms over time [3,4].…”
Section: Introductionmentioning
confidence: 99%